Singapore's Hedging Strategy Amidst US-China Competition - Dhavanda Alifa Fitrah Alamsyah (Department of International Relations, Brawijaya University, 2025)
This study examines how Singapore's hedging strategy amid US-China competition manifests its strategic culture of vulnerability. Through qualitative descriptive analysis of policy documents and elite speeches from 2010-2024, the research identifies two complementary dimensions: hard hedging through institutionalized security cooperation with the United States, and soft hedging through economic integration with China and multilateral diplomacy via ASEAN platforms. The findings demonstrate that Singapore's hedging is not merely tactical response but a systematic manifestation of its deeply embedded vulnerability narrative. By maintaining credible defense capabilities while pursuing economic diversification, Singapore transforms structural weakness into strategic innovation, navigating great power rivalry through sophisticated dual engagement that preserves autonomy and ensures survival.